SEDIMENT TRANSPORT STUDIES ON HOMOGENEOUS SOIL BASE MATERIAL - Revianti Coenraad (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
Sediment transport is the movement of sediment granular material/non cohesive by water flow. Sediment is carried by the flow of water constantly, which can be distinguished as floating sediment (suspended load) and bed load sediment. Sediment transport from upstream to down stream will affect some areas that experienced scour and deposition (sedimentation). This will cause a variety of problem shence it is needed to know the amount of sediment transport since it always moves with the flow.To minimize its negative effects, it is necessary to study the amount of sediment transport with homogeneous base material composed of sand and gravel. This study aimed to determine the effect of water discharge(Q) and the number of stream sediment transported (T) and to knowthe basic condition of the channel due to sediment transport after discharge flowed. The experiment was conducted at the glass channel of Laboratory of Hydrology/Hydraulics, Faculty of Engineering, University of Palangka Raya with dimensions of 400x10x25cm, while the selection of grain grading and inspection of the channel density of the base material such as sand and gravel carried out at the Laboratory of Soil Mechanics, Faculty of Engineering, University of Palangka Raya.The amount of discharge flowed varies with time and the experiment was performed 5 times for each channel base material. The results of the sediment transport studies on materials such as sand and gravel base shows that the greater the flow, the greater also the amount of sediment transported while the smaller debit amounts of sediment transported less. Sand diameter 0.43mm to0.58 mm transported more than the transported gravel with a diameter of2.40mm to 4.75mm, mostly gravel grain rolling and sliding just moves along the baseline. Basic conditions after a transport channel has changed from its original condition with the average basic channels 2.00cm thickness would appear to be a plane bed, washed-out dunes/transition, ripple and dunes.